Evaluación de dos Protocolos de Lactoinducción Hormonal en Vacas del Barrio Santa Rosa de la Parroquia Presidente Urbina del Cantón Santiago de Pillaro. - Samaniego Chamorro, Alex Johan (2019)
The present investigation was carried out at of Santiago de Pillaro city,Presidente Urbina Parish in the Private Property Aleli, with the objective to evaluate two protocols of lactoinduction in milky cows, through the application of hormonal analogues to increase in a short time the number lactating cows, for which 26 virgin cows with weights ranging from 350 to 400 kg were used, which were divided into 2 random groups of 13 animals, after that the progesterone variant was used in the protocols ; at the first treatment, CIDR progesterone 1.38 grams was used, in the second treatment ,Injectable serum progesterone (Gestavec) was used daily at a dose of 0.2mg / kg weigh. There was no difference in the application of estradiol benzoate, Dexamethasone and oxytocin commonly; Obtaining better results in the use of the implant in the hormonal lactoinduction process, same that positively influences the reproduction of cows under treatment, where insemination effectiveness evidenced effectiveness with natural zeal (93.75%), and in the other hand protocol number 2 with injectable progesterone (62.5%) use. In addition in week 1, 3,5 was determined that no statistical difference according to the value p 0.1097; 0,1426; 0,0736 successively in the dairy increase ; for week 2, 4,6 there is a statistical difference of p-value 0.0003, 0.0362, 0.0368 progressive to lactoinduction, statistical and numerical superiority is evident in the implant, so it is proved with successive increase in milky production , stabilizing in 5 week post first milking, period with increasing compared to the normal birth process.